The Influence of the crown and ring land piston dimensions on the performance of the Honda Supra X 125 motorcycle engine - Muhamad Randi Febrian; Boni sena Boni; Siswadi Siswadi; Edlyn Farid Simanjuntak Edlyn; Alwi Azwar Anas Alwi (BKS-TM Indonesia, 2026)
This study aims to analyze the influence of piston crown and ring land dimensions on the performance of a 125 cc engine with a bore of 52.40 mm and a stroke of 57.90 mm. The research scope includes geometric dimension calculations, three-dimensional modeling using SolidWorks, and theoretical engine performance evaluation. The method employed empirical piston design ratios and performance analysis using a Brake Mean Effective Pressure (BMEP) of 900 kPa at 8,000 rpm. The results indicate a cylinder volume of 124.95 cc with piston dimensions consisting of a 4.78 mm crown thickness, 2.62 mm ring land height, 3.14 mm oil ring groove width, 36.68 mm skirt length, and 13.10 mm piston pin diameter. Performance analysis yielded a power output of 6.67 kW (8.94 HP), torque of 7.96 Nm, theoretical thermal efficiency of 59.2%, and an estimated BSFC of 75.7 g/kWh. Overall, the designed piston dimensions are consistent with the characteristics of a 125 cc four-stroke SOHC engine and approach the actual performance of the Honda Supra X 125 engine.